The effectiveness of nurse-led visual rehabilitation on visual outcome among post-operative patients of sellar/suprasellar tumours-protocol of a randomized controlled trial - Bharti; Dhandapani, Manju; Salunke, Parveen; Bansal, Reema; Sukhija, Jaspreet; Dhandapani, Sivashanmugam (International Journal of Clinical Trials, 2025)
Background: Tumour or mass of the suprasellar region are common pathologies and are also important due to their adjacency to the vital anterior visual apparatus. They may cause serious ocular signs and symptoms in addition to neurological complications resulting from increased intracranial pressure, cranial nerve impairment, or brain compression. Increased ICP may lead to headache, double vision and loss of peripheral vision, can lead to sinus pain or ear pain, drooping eyelid and seizures. After surgery, patients may continue to experience neuropsychological symptoms, physical symptoms and develop complications. Methods: Randomized controlled trial. A computer random table with allocation concealment will be used to recruit and assign patients with visual complaints resulting from sellar/suprasellar tumors operated on at PGIMER to the experimental and control groups. Enrolment will be done on 5th to 7th day of surgery and intervention will be provided on the same day until discharge and booklet with nurse-led visual rehabilitation will be provided for continuous practice at home. The post-op follow-up will be done at 1 month and 3rd month of surgery. Conclusions: This aim of the study is to determine the effectiveness of “nurse-led visual rehabilitation” on visual outcome among post-op patient with sellar/suprasellar tumours at 1 month and 3 months. The comprehensive nurse-led visual rehabilitation will be designed with the inputs from all nursing and clinical specialist in neurosurgery and ophthalmology, has the ability to work well with the dynamic care of postoperative patients experiencing visual problems from suprasellar and sellar tumors. CTRI registration number: CTRI/2023/08/056030 ON 2/8/23